Characteristics of Cancer Symptom Clusters Reported through a Patient-Centered Symptom Cluster Assessment. (July 2022) - Kwekkeboom, Kristine L.; Wieben, Ann; Braithwaite, Loyda; Hopfensperger, Kaitlyn; Kim, Kyung Soo; Montgomery, Kathleen; Reske, Margaret; Stevens, Jennifer
In the scope of symptom cluster research, few investigators have obtained patients' perceptions of their symptom clusters, even though this information is central to designing effective interventions. In this cross-sectional study, 38 adults with cancer completed measures of demographics, health outcomes (functional status, well-being, quality of life) and a symptom cluster assessment that captured symptom occurrence, severity, distress, clustering, a priority cluster, causal attributions, duration, directional relationships, and cluster interference with daily life. Participants described 72 distinct symptom clusters. Symptoms were most frequently attributed to the cancer diagnosis. Participants' priority symptom cluster typically included two symptoms of continuous duration and one intermittent symptom. Temporal order and direction of symptom relationships varied, with 75 different relationships described among symptom pairs. Greater symptom cluster burden and interference were related to poorer health outcomes. This patient-centered view of symptom clusters revealed substantial variability in symptom cluster characteristics with important implications for symptom management.